Increase in diagnosed newly acquired hepatitis C in HIV-positive men who have sex with men across London and Brighton, 2002–2006: is this an outbreak?. Issue 2 (11th October 2007) - Giraudon, I; Ruf, M; Maguire, H; Charlett, A; Ncube, F; Turner, J; Gilson, R; Fisher, M; Bhagani, S; Johnson, M; Barton, S
Abstract : Objectives: To determine the incidence of diagnosed newly acquired hepatitis C virus (HCV) in HIV-positive men who have sex with men (MSM) across London and Brighton in order to inform public health interventions. Methods: Cases were defined as MSM attending London and Brighton HIV/genitourinary medicine clinics from January 2002 to June 2006, with HCV PCR RNA or antibody positive, and a negative HCV test in the previous three years. The yearly number of cases and HCV screening policy in MSM were examined. A negative binomial regression model was used to estimate HCV incidence density rate ratio and 95% CI. Results: 20 out of 38 clinics provided information, covering 84% of the HIV-positive MSM workload in London and 100% in Brighton. The estimated overall incidence was 9.05 per 1000 HIV-positive MSM patient-years. It increased from 6.86 per 1000 in 2002 to 11.58 per 1000 during January–June 2006. Incidence at clinics ranged from 0 to 15.4 (median 6.52) per 1000 HIV-positive MSM patient-years. There was some evidence of difference in the incidence and trend (p = 0.02) in each clinic. The average annual rise in incidence of HCV was 20% (95% CI 4% to 39%, p = 0.001). There was little evidence of such transmission among MSM with negative or unknown HIV status. Conclusions: HCV incidence clearly increased among HIV-positive MSM in London and Brighton during January 2002 to June 2006. Prospective enhanced surveillance of HCV in MSM, including HIV status and behavioural risk factors, is recommended to help inform control measures and better determine the frequency of transmission in all MSM.